Sensory Analysis of Steamed Apem With Dragon Fruit Skin Substitution (Hylocereus Polyhizus) - Isra Mutia; Anni Faridah; Lucy Fridayati; Riski Gusri Utami (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The Indonesian traditional moist cake industry including putu cake, lapis cake, and apem cake, still relies heavily on synthetic food colorings that pose health risks. Natural colorings are a safer alternative, as they are often derived from plants or food waste, such as suji leaves, beets, and dragon fruit peel. Red dragon fruit peel (Hylocereus polyrhizus) has potential as a natural dye alternative because it contains high levels of betacyanin, which acts as an antioxidant while also providing a rich color. Steamed apem cake is one of Indonesia's traditional cakes that has cultural value and is widely consumed by the community. Color is one of the factors influencing product attractiveness; however, synthetic food colorants are still commonly used and may pose health risks if used improperly. Natural colorants are a safer alternative and can be obtained from various plants, such as carrots, pandan leaves, and dragon fruit. Red dragon fruit peel, a by-product of the fruit processing industry, contains betalain pigments and has the potential to be utilized as a natural food colorant. This study employed an experimental method using a Completely Randomized Design (CRD) with four treatments: 0%, 35%, 50%, and 65% substitution of dragon fruit peel extract. Product quality was evaluated through ranking and hedonic tests using a 7-point scale by 30 semi-trained panelists. Data were analyzed using Analysis of Variance (ANOVA), followed by Duncan's Multiple Range Test (DMRT) at a 5% significance level when significant differences were detected. The results showed that dragon fruit peel extract substitution significantly affected color quality (F = 69.64 > Ftable = 2.71) and texture (F = 23.60 > Ftable = 2.71), but had no significant effect on shape (F = 0.05 < Ftable = 2.71), aroma (F = 0.82 < Ftable = 2.71), or taste (F = 0.48 < Ftable = 2.71). In the hedonic test, the substitution significantly affected panelists' preference for color (F = 23.91 > Ftable = 2.71) and taste (F = 13.91 > Ftable = 2.71), while no significant effects were observed for shape, aroma, and texture. The best treatment was obtained with 65% dragon fruit peel extract substitution, indicating its potential as a natural food colorant while improving the sensory quality of steamed apem cake.